Wrapping Assembly of BaTiO3 Nanoparticles with (Bi0.5Na0.5)TiO3 Nanosheets: A Novel Processing for Nanograined BT–BNT Complex Perovskite Relaxors. Issue 20 (21st May 2022) - Song, Tae Yeong; Sung, Woojun; Kim, Hanwool; Kim, Baekcheon; Kwon, Do-Kyun
Abstract : Hydrothermal syntheses of BaTiO3 (BT) nanoparticles and (Bi0.5 Na0.5 )TiO3 (BNT) nanosheets are explored to maximize the uniform distributions of the components in BT–BNT complex perovskite solid solution preparation. By introducing a "wrapping process, " which is a 2D nanosheet‐based process for preparing core–shell‐type assembly of the BT and BNT powder mixture, the solid solution formation and densification are accelerated effectively resulting in lowering the sintering temperature and homogeneous nanograined microstructure. The improved microstructure of the BT–BNT solid solution ceramics contributes to the enhancement in dielectric polarizations over a wide temperature range. Relaxor characteristics of the solid solutions, i.e., diffusivity of the ferroelectric–paraelectric transition, frequency dispersion of ε r ′, and shift of T m with frequency deviation from the Curie–Weiss law, are determined. It is also confirmed that the BT–BNT samples prepared by the wrapping process exhibit stronger relaxor behavior compared to the conventionally prepared BT–BNT samples even in the identical chemical composition. These hydrothermal reaction‐based novel processing routes for the complex perovskite compositions are very effective to improve microstructure, sinterability, and dielectric properties. Abstract : By introducing a "wrapping process, " which is a 2D nanosheet‐based process for preparing core–shell‐type assembly of the BaTiO3 (BT) and (Bi0.5 Na0.5 )TiO3 (BNT) powder mixture, the solid solution formation and densification are accelerated effectively resulting in lowering the sintering temperature and homogeneous nanograined microstructure. The improved microstructure of the BT–BNT solid solution ceramics attributes to the enhancement in dielectric polarizations.